Performance of myositis‐specific antibodies detected on myositis line immunoassay to diagnose and sub‐classify patients with suspected idiopathic inflammatory myopathy, a retrospective records‐based review. (11th July 2021) - Beaton, Thomas J.; Gillis, David; Prain, Kerri; Morwood, Karen; Anderson, James; Goddard, John; Baird, Timothy
Abstract: Aim: To evaluate myositis line immunoassay (LIA) for diagnosis and sub‐classification of suspected idiopathic inflammatory myopathy (IIM). To investigate if test performance is improved by increasing signal strength cut‐off for myositis‐specific antibody (MSA) or combining MSA with indirect immunofluorescence (IIF). Methods: A retrospective, consecutive case series of patients investigated for MSAs from June 2013 to June 2020 for suspected IIM. Specificity, sensitivity, positive predictive value, and negative predictive value were calculated with 95% confidence intervals for diagnosis of IIM. Association of IIM diagnosis with increased signal strength and presence of an expected IIF pattern on Hep‐2 cells was assessed by Fisher's exact test in MSA‐positive patients. Results: A total of 195 patients were evaluated. IIM was diagnosed in 32/195 (16.4%) patients. MSAs were detected in 41/195 (21%) patients, 18/41 (43.9%) patients with an MSA had a diagnosis of IIM. The probability of an IIM diagnosis was increased in MSA‐positive patients with high compared with low signal strength (83.3% vs 43.5%; P = 0.01) and an expected compared with unexpected IIF pattern (61.5% vs 23.8%; P = 0.04). Specificity for IIM was not significantly improved by increasing signal strength cut‐off (85.9% vs 93.8%). Positive predictive value of myositis LIA was only modest and not significantly improved by either increasing signal strength cut‐off or requiring an expected IIF pattern for determination of MSA positivity (43.9% vs 60% vs 61.5%). Sub‐classification of IIM correlated closely for respective MSAs (88.9%). Conclusion: Increased MSA signal strength on myositis LIA and the presence of an expected IIF pattern were associated with IIM diagnosis. Test performance was non‐significantly improved by these methods. Prevalence of IIM in this patient cohort was low; it is not excluded that LIA performance could be improved by these methods in a higher prevalence cohort.